2018
DOI: 10.1007/s00467-018-4050-z
|View full text |Cite
|
Sign up to set email alerts
|

Renal function and blood pressure are altered in adolescents born preterm

Abstract: Prematurity was associated with higher BP and reduced renal function that were detectable in adolescence. OWO and sex may modify the strength of these relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 40 publications
(48 reference statements)
6
59
1
1
Order By: Relevance
“…This can be an issue in women born with very low birth weight, a population known to have a reduced nephron number and to be particularly prone to developing FSGS. [17][18][19][20][21] These studies point to the importance of hemodynamic factors, namely pregnancyrelated hyperfiltration, in the pathogenesis of lesions. However, in keeping with what has been observed in patients with cancer treated with antiangiogenic drugs, it is possible that the imbalance between angiogenic and antiangiogenic factors is a contributing factor.…”
Section: Introductionmentioning
confidence: 99%
“…This can be an issue in women born with very low birth weight, a population known to have a reduced nephron number and to be particularly prone to developing FSGS. [17][18][19][20][21] These studies point to the importance of hemodynamic factors, namely pregnancyrelated hyperfiltration, in the pathogenesis of lesions. However, in keeping with what has been observed in patients with cancer treated with antiangiogenic drugs, it is possible that the imbalance between angiogenic and antiangiogenic factors is a contributing factor.…”
Section: Introductionmentioning
confidence: 99%
“…Our study identified dysregulated blood pressure as a long-term consequence of premature birth, with transgenerational inheritance up to the third generation. Several studies have already reported high blood pressure in former preterm infants, as early as in infancy or adolescence 7 . Developmental programming of cardiovascular diseases was first described by Barker et al, who proposed that early events occurred during the perinatal period, i.e., preterm birth could adversely impact organogenesis or ontogenesis of signaling pathways and be responsible for long-term cardiovascular alterations in adulthood 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Renal developmental alterations may also impact renal structure and function until adulthood and induce compensatory glomerulomegaly, renin-angiotensinaldosterone system (RAAS) activation and glomerulosclerosis, according to the Brenner hypothesis 6 . Former preterm infants are indeed prone to developing hypertension, as early as in adolescence 7 , which leads to a global cardiovascular risk increase in this population.…”
Section: Introductionmentioning
confidence: 99%
“…La asociación entre RN prematuro y presión arterial (PA) más elevada parece estar bien establecida, aunque no claramente como hipertensión arterial (HTA), para lo cual podría requerirse más tiempo de seguimiento 1,2,13,15 . En el caso de adolescentes y adultos jóvenes nacidos prematuramente varios estudios han observado mayores tasas de PA elevada e HTA, e inversamente proporcional a la prematurez del nacimiento 16,17 . En un pequeño estudio local en escolares nacidos muy prematuramente (menores de 32 sema-nas EG o menos de 1.500 g al nacer), el registro de monitoreo ambulatorio de PA (MAPA) demostró una alta prevalencia de alteraciones, principalmente la ausencia de diferencia de PA día vs noche, lo que se relaciona con mayor riesgo de progresión a HTA 18 .…”
Section: A Hipertensión Arterialunclassified